Relationship between microplastics and cardiovascular risk factors - M. N. Mamedov; E. A. Savchuk (Кардиоваскулярная терапия и профилактика)
In recent years, plastic has been widely used in various anthropic activity fields, but its waste pollutes the environment. Under the influence of chemical processes, it decomposes micro- and nanoplastics, which enter the human body in various ways. New experimental studies indicate that they can cause a number of cardiovascular disorders, including endothelial cell dysfunction and induction of oxidative processes.The article examines the impact of environmental pollution with microplastics on the development of cardiovascular diseases. It is clear that new data on this new risk factor are accumulating and further clinical studies are required.